2004
DOI: 10.5194/aab-47-551-2004
|View full text |Cite
|
Sign up to set email alerts
|

Connection of milk flow curve to the somatic cell count in bovine milk

Abstract: The modern equipment introduction into cow milking created technical possibilities for studying the milk flow curve and for using the results in cattle selection. In preventing mastitis, besides curing, other parameters of the milk flow curve could be used preventively. Research showed that cows that had the milk flow curve with a short duration of increasing flow rate (dIFR≤0.40 min) and a larger quotient between the peak and down phase (QPD>1.20) had also the least somatic cell count in milk (LSCC = 3.47, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…The weak correlation (−0.05) between milking duration and SCS in the present study is consistent with previous studies in Italian Holstein-Friesian dairy cows (−0.05; Samoré et al, 2011) and Italian Brown Swiss cows (−0.02; Gray et al, 2011) as well as in Irish dairy cows of alternative breeds (−0.09; Prendiville et al, 2010) and Croatian Holstein-Friesian cows (−0.08; Miji et al, 2004). Weak phenotypic correlations (0.02 to 0.06) have also been reported between SCS and subjectively scored milking speed (Boettcher et al, 1998); for the subjective measures of milking speed, a higher phenotypic value reflects faster milking.…”
supporting
confidence: 95%
See 1 more Smart Citation
“…The weak correlation (−0.05) between milking duration and SCS in the present study is consistent with previous studies in Italian Holstein-Friesian dairy cows (−0.05; Samoré et al, 2011) and Italian Brown Swiss cows (−0.02; Gray et al, 2011) as well as in Irish dairy cows of alternative breeds (−0.09; Prendiville et al, 2010) and Croatian Holstein-Friesian cows (−0.08; Miji et al, 2004). Weak phenotypic correlations (0.02 to 0.06) have also been reported between SCS and subjectively scored milking speed (Boettcher et al, 1998); for the subjective measures of milking speed, a higher phenotypic value reflects faster milking.…”
supporting
confidence: 95%
“…Irrespective of the definition of milking duration or milking speed, most studies appear to agree that faster-milking animals have greater SCS, which may be due to decreased tension of the teat sphincter muscle, thereby providing a weaker barrier to infection. Corroborating the weak correlations between both AMF and MMF rate with SCS in the present study (−0.08 to 0.01), weak correlations (−0.03 to 0.13) were also reported between the flow rate traits and SCS in other dairy cow populations (Miji et al, 2004;Prendiville et al, 2010;Gray et al, 2011;Samoré et al, 2011). Grindal and Hillerton (1991) reported greater mastitis incidence in quarters with greater milk peak flow rates.…”
supporting
confidence: 59%
“…Other advantages of ultrasonography for evaluating intramammary tissues are its ease of use and being non‐invasive 8,12,16–18 . Ultrasonographic techniques can be used to determine the intramammary factors that may lead to the development of mastitis and these factors should be taken into consideration in the control and prevention of mastitis 13,16,19–22 …”
mentioning
confidence: 99%
“…8,12,[16][17][18] Ultrasonographic techniques can be used to determine the intramammary factors that may lead to the development of mastitis and these factors should be taken into consideration in the control and prevention of mastitis. 13,16,[19][20][21][22] The objective of the current study was to determine the relationship between ultrasonographic udder and teat measurements and California Mastitis Test (CMT) scores. In addition, the effects of breed, age, number of lactations, the lactation period, udder lobe (front, rear), pregnancy, and CMT score on these measurements were evaluated.…”
mentioning
confidence: 99%
“…Several reports (e.g. NAUMANN et al, 1998;RUPP and BOICHARD, 1999;NAUMANN and FAHR, 2000;MIJC et al, 2004), concluded that milking ease was found to be low inheritable and unfavorably correlated with udder health. Desirable high milking speed (or milking ease) has been reported to be associated with an undesirable high somatic cell count (SEYKORA and MCDANIEL, 1986;BOETTCHER et al, 1998;MIJC et al, 2004).…”
mentioning
confidence: 99%